Management of hereditary breast cancer: Surgeon's perspective - Ava Kwong (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Mutations due to hereditary related genes such as BRCA1, BRCA2, TP53 and PTEN confer greater risk of developing breast cancer and for BRCA mutations, also ovarian cancer. The risk assessment based on genetic testing allows options of high risk surveillance, prevention and may now also guide use of specific therapies for treatment such as targeted therapies and use of platinum base chemotherapy. The choice of management, once an individual has been found to carry the BRCA mutation may also vary. Moreover the availability of genetic testing, method of testing such as the transition into the use of Next Generation Sequencing techniques has also increased options of clinicians to the choice of testing.Breast Surgeons are most likely to be the first person who encounters the first presentation of a breast cancer patient. It is important for breast surgeons to be actively involved in the referrals of patients for genetic testing and subsequently planning of the management of such high risk individuals in a multidisciplinary setting. Basic principles of genetic testing and choice of management will be discussed in reference to the surgeon’s perspectives. Keywords: mutations, BRCA1. BRCA2. TP53, PTEN, NGS, multidisciplinary setting